Organization of strategic management of potential of corporate logistics systems organizing on the basis of marketing - Пилипенко, Діана Рафаелівна (Technology audit and production reserves, 2015)
One of the popular trends of the national economy is the development of cooperative-integrative processes that lead to the emergence of corporate logistics systems. Based on its own working, the author argues the need for proper organization for strategic management of logistics systems. The basis of the proposed organizational process is in correlating of levels of marketing and logistics capacity. Proof of the proposition is based on constructing a model of canonical correlation based on the proposed list of indicators. The practical implementation of the proposed combination of targeting potential marketing and logistics invited to perform by building relevant strategic matrix. Empirical rationale of such matrix formation and establishment of the list of its segments is cluster analysis of 31 enterprises of engineering industry. Preconditions of strategic management of corporate logistics system, depending on the segment developed strategic matrix are determined in the article based on the results of this analysis.